Educational effects of Chilean government guidelines in a COVID-19 pandemic context - Saavedra, Esteban; Zapata-Zapata, Viviana; Rojas-Mora, Julio (Revista de Inclusión Educativa y Diversidad (RIED), 2024)
As a result of the COVID-19 pandemic, the Chilean government decreed the suspension of classes in all educational institutions. The objective of the present article is to investigate the direct and indirect effects of the governmental guidelines on students' learning. The research method has a constructivist epistemological approach from the modified neglected effects theory. The main results show that emotional restraint would be the most influential “polyfunctional” action on all dimensions of student learning; and indirectly, making the curriculum and assessments more flexible for students would have an indirect effect on their social development and value formation. In conclusion, the modified neglected effects theory allowed us to com-prove that state orientations in the pandemic context have influenced school learning in Chile.
Keywords: COVID-19; Educational development; Forgotten effects; Wicked problems; Education policies